2017
DOI: 10.1073/pnas.1708991114
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional resemblance of differentiated cells derived from isogenic human iPSCs and SCNT-derived ESCs

Abstract: Patient-specific pluripotent stem cells (PSCs) can be generated via nuclear reprogramming by transcription factors (i.e., induced pluripotent stem cells, iPSCs) or by somatic cell nuclear transfer (SCNT). However, abnormalities and preclinical application of differentiated cells generated by different reprogramming mechanisms have yet to be evaluated. Here we investigated the molecular and functional features, and drug response of cardiomyocytes (PSC-CMs) and endothelial cells (PSC-ECs) derived from geneticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 42 publications
3
44
0
Order By: Relevance
“…Functional annotation clustering was performed on protein-coding genes upregulated by more than 5-fold in the EoE sample set (false discovery rate, <0.1). [24][25][26] Quantitative RT-PCR assays RNA was isolated from esophageal biopsy specimens for quantitative realtime RT-PCR, as described previously, 14 by using TaqMan Gene Expression Assays (Thermo Fisher Scientific, Waltham, Mass) for LOX (Hs00942483) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH; Hs99999905_m1), the latter as an internal control gene.…”
Section: Rna-sequencing Data Analysesmentioning
confidence: 99%
“…Functional annotation clustering was performed on protein-coding genes upregulated by more than 5-fold in the EoE sample set (false discovery rate, <0.1). [24][25][26] Quantitative RT-PCR assays RNA was isolated from esophageal biopsy specimens for quantitative realtime RT-PCR, as described previously, 14 by using TaqMan Gene Expression Assays (Thermo Fisher Scientific, Waltham, Mass) for LOX (Hs00942483) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH; Hs99999905_m1), the latter as an internal control gene.…”
Section: Rna-sequencing Data Analysesmentioning
confidence: 99%
“…A previous report indicated that the ability of mouse NT-ESCs to form hematopoietic colonies is greater than the corresponding capacity of isogenic iPSCs 32 . Recently, Zhao et al 33 demonstrated the functional similarity of cardiomyocytes and endothelial cells derived from isogenic human iPSCs and NT-ESCs. However, both prior studies only evaluated the cell fate potential of the mesodermal lineage.…”
Section: Discussionmentioning
confidence: 99%
“…As iPSCs are derived from adult tissue rather than embryonic tissue, they avoid the ethical issues associated with ESCs. No significant differences in gene expression levels, surface marker expression, and morphology between ESCs and iPSCs are observed in cells from the same genetic background [131,132]. In addition to circumventing ethical controversies, another advantage of iPSCs over ESCs is that they can be obtained from donors of known disease phenotypes, which can be used for patientspecific disease models and drug screening.…”
Section: Stem Cell Engineeringmentioning
confidence: 99%